Acceptance- and Mindfulness-Based Interventions for Health Behavior Change: Systematic Reviews and Meta-Analyses - Roche, Anne I. (J Contextual Behav Sci, 2019)
Behavioral health issues such as smoking and overweight are risk factors for a variety of adverse health outcomes, including mortality. Over the past decade, a growing number of randomized controlled trials have examined the efficacy of acceptance- and mindfulness-based interventions for smoking cessation and weight loss. The purpose of the current meta-analytic reviews was to quantitatively synthesize the existing literature comparing these interventions to controls for a) smoking cessation and b) weight loss outcomes. Searches identified 17 smoking cessation studies and 31 weight loss studies eligible for inclusion. Meta-analytic results indicated a non-significant effect favoring acceptance- and mindfulness-based interventions over controls for smoking cessation (OR = 1.13) and a small, significant effect favoring these interventions over controls for weight loss outcomes (Hedge’s g = 0.30). Statistical heterogeneity and risk of bias were assessed. Subgroup and meta-regression analyses were conducted to examine moderating variables (e.g., sample and intervention characteristics). The findings indicated that acceptance- and mindfulness-based interventions were at least as efficacious as active control conditions. Given the significant health risks associated with smoking and overweight, these findings have important clinical and public health implications. Limitations (e.g., relative infancy of the literature; lack of diversity in sample demographics) and future directions (e.g., further exploration of mediators and moderators of change) are discussed.